FAKTOR DOMINAN YANG MEMENGARUHI KELELAHAN KERJA PADA PEKERJA DIBAGIAN TIANG PANCANG DI BANDUNG BARAT DIBAGIAN TIANG PANCANG DI BANDUNG BARA - Syuhada, Ambar Dani; Widodo, R. Setijo (MEDIA ILMU KESEHATAN, 2019)
Background: Work exhaustion is a feeling of fatigue and decreased alertness. Factors that cause work fatigue are related to the monotonous nature of work, work intensity, and high mental and physical work resistance, workroom weather; lighting and noise and inadequate work environment, psychological factors, nutritional status, and cardiac rhythm Objective This study aims to find out the dominant factors affecting work fatigue in pole production workers at PT. X Year 2018 Methods: This research method used is a cross-sectional study. The research samples used was a total sampling of 35 respondents. Data collection is done through observation and measurement. The instruments used in the study were questionnaire KAUPK2, Sound Level Meter, Reaction Time, REBA and Pulse Meter. Bivariate data analysis used chi-square and multivariate used logistic regression Results: Bivariate analysis that the variables of age, noise, workload, and work attitudes had a significant relationship with work fatigue (p <0.05) while work period variables, body mass index had no significant relationship with work fatigue. (p> 0.05). Conclusion: The company is expected to set a working hour with a schedule of 8 hours starting from the hours of entry, hours of rest, hours of return, scheduled leave to overtime. And do periodic checks.